Madrasah Leadership in Improving Teacher Performance in MTs Imam Puro Kutoarjo, Purworejo - Samrowi Samrowi (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2019)
This research is based on the problem of unsatisfactory teacher performance. In relation with regard to this study aims to determine the leadership of the madrasa head in improving teacher performance at MTs Imam Puro Kutoarjo, Purworejo Regency. This research using qualitative research that focuses on natural and empirical phenomena analyzed using scientific logic thinking. The data collection techniques on this research was obtained through observation, interviews, documentation, and triangulation. Data analysis done by data reduction, data presentation, and data verification then formulate conclusions of the results of research conducted. There are three findings in this study, namely: (1) executive power of the head leadership Madrasas have been proven to produce products, the vision and mission of Madrasas have been implemented properly well, although still on a small scale, to achieve the teacher's performance criteria and objectives This education requires the cooperation and role of the madrasa head, growing develop the characteristics of madrasas with a 5S culture in madrasas and teachers carrying out their duties and responsibilities professionally, has a good personality and can be a role model students, have a high social and societal spirit; (2) legislative power the leadership of the madrasa head as law maker in improving teacher performance in MTs Imam Puro Kutoarjo is proven by fostering and managing community relations between schools; become an agent of change, actively make changes, seek new breakthroughs, mobilizing its members for the advancement of madrasas; able to enforce laws, regulations, and madrasa policy as an effort to improve school quality; preparation of school policies, apply the principle of participation and interaction between policy makers, policy implementers, and stakeholders and carried out by taking into account management functions; (3) decision-making power of the madrasah leadership as a policy maker and achievement of goals that have been set together and role models or central figures who are all his actions, attitudes, deeds, and words set an example for the teachers he leads